1999
DOI: 10.1046/j.1365-2958.1999.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the antigen 85C gene profoundly affects the mycolate content and alters the permeability of the Mycobacterium tuberculosis cell envelope

Abstract: SummaryThe antigen 85 complex of Mycobacterium tuberculosis consists of three abundantly secreted proteins. The recent characterization of a mycoloyltransferase activity associated in vitro with each of these antigens suggested that they are potentially important for the building of the unusual cell envelope of mycobacteria. To define the physiological role of these proteins, the gene coding for antigen 85C was inactivated by transposon mutagenesis. The resulting mutant was shown to transfer 40% fewer mycolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
267
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(286 citation statements)
references
References 51 publications
11
267
2
6
Order By: Relevance
“…These data indicated that the diffusion of these antibiotics through the cell wall barrier was not the limiting step for their activity. A similar observation has been made for the fbpC-inactivated mutant of Mycobacterium tuberculosis, which exhibited a change in its cell wall permeability to chenodeoxycholate due to a 40 % reduction of covalently linked mycolates (Jackson et al, 1999).…”
Section: Cell Wall Permeability Of the Mutantsupporting
confidence: 73%
See 2 more Smart Citations
“…These data indicated that the diffusion of these antibiotics through the cell wall barrier was not the limiting step for their activity. A similar observation has been made for the fbpC-inactivated mutant of Mycobacterium tuberculosis, which exhibited a change in its cell wall permeability to chenodeoxycholate due to a 40 % reduction of covalently linked mycolates (Jackson et al, 1999).…”
Section: Cell Wall Permeability Of the Mutantsupporting
confidence: 73%
“…Although no sign of a second lipid bilayer has ever been reported in thin sections of mycobacterial cells (Draper, 1998), freeze-fractured samples of mycobacteria (Barksdale & Kim, 1977 ;Benedetti et al, 1984 ;Takeo et al, 1984) showed that these organisms had two such planes of weakness in their envelopes ; in addition to the expected plasma membrane fracture, a second fracture plane, close to the cell surface of mycobacteria, was observed. The cell wall-linked mycolates certainly participate in this barrier since the disruption of a gene that encodes a mycoloyltransferase, namely antigen-85C, causes a decrease in the amount of cell wall-bound mycolates and affects the permeability of the envelope of the mutant (Jackson et al, 1999). Evidence has also been presented that the chemical structure of mycolic acids plays a role in determining the fluidity and permeability of the mycobacterial cell wall (George et al, 1995 ;Liu et al, 1996 ;Dubnau et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the Mycobacterium tuberculosis mutant of the fbpA gene, a homolog of C. glutamicum cspA, showed increased uptake of hydrophilic glycerol and of hydrophobic chenodeoxycholate. 29) It has also been reported that the M. tuberculosis mutant of the kasB gene involved in mycolic acid synthesis showed increased sensitivity to several antibiotics. The C. glutamicum cspA mutant strain also showed a faster uptake rate of hydrophilic compounds, including glycerol and acetate.…”
Section: Discussionmentioning
confidence: 98%
“…33) It has also been reported that the M. tuberculosis fbpA mutant showed faster uptake of hydrophobic chenodeoxycholate. 29) These phenomena are to be explained by analogy with the outer membrane of Gram-negative bacteria. Lipopolysaccharides occupy the outer leaflet of the outer membrane and form a highly ordered quasicrystaline structure with very low fluidity.…”
Section: Discussionmentioning
confidence: 99%